2011
DOI: 10.1177/1077546311407648
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study on nonlinear vibration of an inclined cable coupled with the deck in cable-stayed bridges

Abstract: The mechanism and the characteristics of the cable-deck coupled nonlinear vibration in a cable-stayed bridge are studied using numerical methods. A simple three-degrees-of-freedom (d.f.) model, with one independent d.f. for modeling the bridge deck movement, is proposed for describing the nonlinear interactions between the in-plane/out-of-plane vibration of the cable and the oscillation of the bridge deck. The governing equations are discretized with the Galerkin method and then solved with a numerical time in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Several works were carried out to investigate the vibrational behavior of cables (Cheng and Dong, 2016; Kangas et al, 2012; Kim and Jeong, 2005; Papadopoulos et al, 2012). Kang et al (2012) and Dan et al (2014) studied the inclined cables, and fibre reinforced polymer cables are also investigated for the vibration characteristics (Mei et al, 2018; Yang et al, 2014; Zhang et al, 2011). The slackness, fatigue, and fracture problem in cables were investigated by Wu et al (2003), Pellegrino et al (2010), and Suh and Chang (2000), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Several works were carried out to investigate the vibrational behavior of cables (Cheng and Dong, 2016; Kangas et al, 2012; Kim and Jeong, 2005; Papadopoulos et al, 2012). Kang et al (2012) and Dan et al (2014) studied the inclined cables, and fibre reinforced polymer cables are also investigated for the vibration characteristics (Mei et al, 2018; Yang et al, 2014; Zhang et al, 2011). The slackness, fatigue, and fracture problem in cables were investigated by Wu et al (2003), Pellegrino et al (2010), and Suh and Chang (2000), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Kong et al offered a new procedure of sub-structure method to long-span hybrid cable-stayed model bridges subjected to the vibrations due to vehicles [34]. A numerical investigation on the nonlinear vibration of inclined cables coupled with the deck in cable-stayed bridges was done by Kang et al [35]. It was indicated that the periodic variation of the cable tension induced by the deck vibration would cause the parametric resonance of the stay cable under certain tuning conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They developed theoretical models for the vibrations of the cables subjected to support excitations, respectively. In general, vibration models can be classified into a single-cable vibration model (Lilien and Pinto Da Costa, 1994; Chen et al., 2002; Sun et al., 2003; Wu et al., 2003; Mei et al., 2007; Ying et al., 2007; Wang and Zhao, 2009; Kang et al., 2016; Ouni and Kahla, 2012; Brzakala and Herbut, 2014; Sun et al., 2014; Qian et al., 2014; Guo et al., 2016; Warminski et al., 2016) and cable-deck coupling vibration model (Luo et al, 2010; Kang et al., 2012; Sun et al., 2017). In addition, support excitations include the following: horizontal excitation at the upper support of the cable, vertical excitation at the lower support or axial excitation.…”
Section: Introductionmentioning
confidence: 99%